An Analysis of the Effect of WiFi Scanning Interval and Pedestrian Walking Speed on Indoor Localization Performance - Nguyễn, Hữu Khánh (2023)
Recently, in the field of indoor localization, wireless radio and dead reckoning techniques are two main branches that received much attention. The former one uses the wireless facility such as WiFi or Bluetooth to estimate the user position in two ways: triangulation and fingerprinting. The latter one uses the inertial sensors to estimate the displacement of the user based on the previous position. In this paper, from several experiments, we pointed out the effect of WiFi scanning interval and pedestrian walking speed to the positioning result. We also used the WiFi fingerprinting technique as a clue to compensate for the accumulated error of the pedestrian dead reckoning system which is implemented on a smartphone to analyze the effect of the two factors above.